Lupta afro-americanilor in Statele Unite – Civil power or Black Power? - Ana-Maria VARLAN (Perspective Politice, 2017)
The society we live in today has been profundly shaped by the clash of cultures and civilizations and more recently, by ideological conflicts. It is also the case of the United States of America, whose history and evolution was marked by the continuous reglementations of the structure and relations between the white americans and the afro-americans: the Civil Rights Movement and the Black Power movement The following paper aims to explore this issue through the lenses of two important race theories,both sharing a very important concept when discussig racial conflict -double consciousness, each of them being linked to a main afro-american movement in the USA. I shall try to understand how the concept of race and the attempts to fight racism within the american society in the 20th century, have influenced the political discourse and also, the social and cultural context, throughout the last decades. In doing so, i will draw inspiration from the socio-historical constructivist race theory in explaining the evolution and impact of the Civil Rights Movement, and from Fanon’s critical theory in exploring the evolution and the outcome of the Black Power Movement. The main thesis of this paper is that, starting with the end of the 19th century, all the eliberation and empowerment efforts of the black community in the american society, coagulated in the mentioned ideological movements, had a powerfull impact on the social, cultural and political evolution of the United States, materialised in the introduction of Black Studies in universities, political representation and electoral winnings – culminating with the election of Barack Obama as the President of the USA.